2021
DOI: 10.5194/acp-2021-582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced ice number concentrations in contrails from low aromatic biofuel blends

Abstract: Abstract. Sustainable aviation fuels can reduce contrail ice numbers and radiative forcing by contrail cirrus. We measured apparent ice emission indices for fuels with varying aromatic content at altitude ranges of 9.1–9.8 km and 11.4–11.6 km. Measurement data were collected during the ECLIF II/NDMAX flight experiment in January 2018. The fuels varied in both aromatic quantity and type. Between a sustainable aviation fuel blend and a reference fuel Jet A-1, a maximum reduction in apparent ice emission indices … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The nvPM acts as the primary source of condensation nuclei in the "soot-rich" regime, defined when the soot number emissions index (EIn) exceeds 10 13 kg -1 , while ambient aerosols, organic and sulfuric particles can nucleate under "soot-poor" conditions (EIn < 10 13 kg -1 ). Most kerosene-burning aircraft engines typically have nvPM EIn of 10 14 -10 16 kg -1 (EASA, 2021; Petzold et al, 1999;Moore et al, 2017;Durdina et al, 2017), and for these aircraft types, in-situ measurements and modelling studies show that the nvPM EIn influences various contrail properties and associated climate forcing (Voigt et al, 2021;Bräuer et al, 2021b;Teoh et al, 2022a;Jeßberger et al, 2013;Kärcher, 2016). However, there is a small but increasing share of aircraft types powered by staged combustors with nvPM EIn as low as ~10 11 kg -1 (EASA, 2021; Boies et al, 2015), for which the initial contrail properties need further investigation (Voigt et al, 2022).…”
mentioning
confidence: 99%
“…The nvPM acts as the primary source of condensation nuclei in the "soot-rich" regime, defined when the soot number emissions index (EIn) exceeds 10 13 kg -1 , while ambient aerosols, organic and sulfuric particles can nucleate under "soot-poor" conditions (EIn < 10 13 kg -1 ). Most kerosene-burning aircraft engines typically have nvPM EIn of 10 14 -10 16 kg -1 (EASA, 2021; Petzold et al, 1999;Moore et al, 2017;Durdina et al, 2017), and for these aircraft types, in-situ measurements and modelling studies show that the nvPM EIn influences various contrail properties and associated climate forcing (Voigt et al, 2021;Bräuer et al, 2021b;Teoh et al, 2022a;Jeßberger et al, 2013;Kärcher, 2016). However, there is a small but increasing share of aircraft types powered by staged combustors with nvPM EIn as low as ~10 11 kg -1 (EASA, 2021; Boies et al, 2015), for which the initial contrail properties need further investigation (Voigt et al, 2022).…”
mentioning
confidence: 99%
“…In addition to the CO 2 benefits, SAF can also reduce the nonvolatile particulate matter (nvPM) number emissions index (EI n ) by up to 70% relative to conventional fuels, with the reduction in nvPM EI n varying as a function of engine thrust settings, fuel hydrogen, and aromatic content. , nvPM emissions at cruise altitudes contribute to contrail formation when conditions in the exhaust plume satisfy the Schmidt–Appleman criterion (SAC). In the soot-rich regime (EI n > 10 13 kg –1 ), the nvPM EI n is positively correlated with the initial contrail ice crystal number and optical depth (τ contrail ) and negatively correlated with the ice crystal size. , Indeed, recent in situ measurements of young contrail properties , found that replacing conventional jet fuel with SAF led to significant differences in the ice number concentration (up to −70%), ice crystal size (+40%), and τ contrail (−52%), and these changes are expected to reduce the contrail lifetime and climate forcing. However, several studies , estimate that SAF could increase the contrail occurrence by 1–8% because its water vapor emissions index (EI H 2 O ) can be up to 10% higher than that of conventional fuels. ,, While the effects of SAF on contrail occurrence and changes to contrail properties have been measured, the effects of a lower nvPM EI n on the contrail cirrus net radiative forcing (RF) have so far only been quantified with modeling studies: Schumann et al computed a 39% reduction in global annual mean contrail cirrus net RF for a 50% reduction in nvPM EI n ; Bock & Burkhardt and Burkhardt et al found 15 and 50% reduction in the global contrail cirrus net RF, respectively, when SAF is used across the fleet; and Caiazzo et al reported a −4 to +18% change in the contrail net RF over the United States.…”
Section: Introductionmentioning
confidence: 99%
“…24 − 26 In the soot-rich regime (EI n > 10 13 kg –1 ), the nvPM EI n is positively correlated with the initial contrail ice crystal number and optical depth (τ contrail ) and negatively correlated with the ice crystal size. 24 , 27 Indeed, recent in situ measurements of young contrail properties 23 , 28 found that replacing conventional jet fuel with SAF led to significant differences in the ice number concentration (up to −70%), ice crystal size (+40%), and τ contrail (−52%), and these changes are expected to reduce the contrail lifetime and climate forcing. 29 33 However, several studies 34 , 35 estimate that SAF could increase the contrail occurrence by 1–8% because its water vapor emissions index (EI H 2 O ) can be up to 10% higher than that of conventional fuels.…”
Section: Introductionmentioning
confidence: 99%